ARID3A promotes the chemosensitivity of colon cancer by inhibiting AKR1C3. (16th March 2022) - Li, Yafei; Tang, Jing; Li, Jing; Du, Yaru; Bai, Fuqiang; Yang, Lirui; Li, Xiaobo; Jin, Xiaoming; Wang, Tianzhen
Abstract: ARID3A is upregulated in colorectal cancer and can promote the proliferation and metastasis of cancer cells. However, patients with higher level of ARID3A have a better prognosis. This study aimed to uncover the mechanism by which ARID3A benefits the prognosis of colon cancer. Our results indicated that ARID3A upregulation enhanced the chemosensitivity of colon cancer cells to 5‐fluorouracil (5‐FU), whereas ARID3A downregulation inhibited the chemosensitivity of colon cancer cells to 5‐FU. Through database analysis, we found that AKR1C3, a drug resistance‐related gene, was the target of ARID3A. Moreover, AKR1C3 was downregulated in colon cancer tissues compared to normal tissues. Next, we assessed the interaction between AKR1C3 and ARID3A, and found that ARID3A inhibited the transcription of AKR1C3, leading to the downregulation of AKR1C3 in colon cancer cells. We also verified that AKR1C3 inhibited the chemosensitivity of colon cancer cells to 5‐FU. Moreover, patients with higher ratio of ARID3A to AKR1C3 had a better prognosis. This study suggested that ARID3A promoted chemosensitivity of colon cancer cells by inhibiting AKR1C3 in colon cancer. The ratio of ARID3A to AKR1C3 is a good marker to predict the prognosis of colon cancer patients.